2D Titania–Carbon Superlattices Vertically Encapsulated in 3D Hollow Carbon Nanospheres Embedded with 0D TiO2 Quantum Dots for Exceptional Sodium‐Ion Storage. Issue 40 (30th August 2019) - Xia, Qingbing; Lin, Zeheng; Lai, Weihong; Wang, Yongfei; Ma, Cheng; Yan, Zichao; Gu, Qinfen; Wei, Weifeng; Wang, Jia‐Zhao; Zhang, Zhiqiang; Liu, Hua Kun; Dou, Shi Xue; et al.
Abstract: Two‐dimensional (2D) superlattices offer promising technological opportunities in tuning the intercalation chemistry of metal ions. Now, well‐ordered 2D superlattices of monolayer titania and carbon with tunable interlayer‐spacing are synthesized by a molecularly mediated thermally induced approach. The 2D superlattices are vertically encapsulated in hollow carbon nanospheres, which are embedded with TiO2 quantum dots, forming a 0D‐2D‐3D multi‐dimensional architecture. The multi‐dimensional architecture with the 2D superlattices encapsulated inside exhibits a near zero‐strain characteristic and enriched electrochemical reactivity, achieving a highly efficient Na + storage performance with exceptional rate capability and superior long‐term cyclability. Abstract : Well‐ordered 2D superlattices of monolayer titania and carbon vertically encapsulated in hollow carbon nanospheres are embedded with TiO2 quantum dots to form a 0D‐2D‐3D multi‐dimensional architecture. Benefiting from the intriguing merits of 2D superlattices and the synergistic effects of each building block, the multi‐dimensional architecture shows highly efficient Na + storage performance.